Caught in the loop: Faculty narratives on challenges with institutional research committees - Kotsokoane, Frida Mafuri; Seeletse, Solly Matshonisa (Educational Challenges, 2025)
Purpose: This study addresses critical inefficiencies in higher education institutions’ [HEI’s] research committee processes such as delays, poor communication, and outdated workflows that hinder productivity and cause faculty frustration. It aims to propose solutions like digitalization and improved monitoring to enhance Institutional Review Boards [IRB] effectiveness and research outcomes. Methodology: A narrative inquiry approach was used in this qualitative study, which stretched from 2021 to 2024. It used semi-structured interviews with ten faculty members to explore their lived experiences with research committee processes at a Gauteng HEI. Results: The study exposed critical issues that include delays in feedback, poor communication, opaque processes, lack of researcher support, sudden postponements, slow certificate renewals, inadequate monitoring, and structural inefficiencies linked to office separation and lack of digitalization. Conclusion: The study recommendations include implementing turnaround times, improving communication and transparency, digitalizing processes, enhancing researcher support, formalizing meeting schedules, introducing continuous monitoring, clarifying office roles, and nurturing cross-institutional collaboration to improve committee efficiency and researcher experience.